What promotes cognitive dissonance among anti-vaccine members in Indonesia? - Muhammad Husni Thamrin; Oemar Madri Bafadhal; Anang Dwi Santoso (International Journal of Public Health Science (IJPHS), 2023)
This study aimed to examine the influence of expectations on vaccines, trust in government, perceived threats, and information overload to cognitive dissonance and its implications for vaccine use, behavioral negotiation, and information avoidance. After we formulated eight hypotheses, all of them was tested using the partial least squares structural equation modeling (PLS-SEM) method. This study involved 173 community members to fill out a questionnaire with 31 questions. The results showed that expectations of vaccines and information overload affected cognitive dissonance. In contrast, the perceived threat due to the COVID-19 pandemic and trust in the government did not affect cognitive dissonance. We also found that cognitive dissonance negatively and significantly affected vaccine use and positively and significantly affected behavior to continue negotiating and avoiding information related to COVID-19 vaccination. This study is among the first to examine members of the anti-vaccine community quantitatively and practically attempts to intervene in the anti-vaccine community so that they are cognitively dissonant are to increase expectations of vaccination and confuse them by presenting the information overload they receive.